Multidisciplinary Dentistry - Ceramic Laminate Veneers for Orthodontic Finalization - Clinical Case Report - Joao Mauricio Ferraz da Silva; Juliana da Costa Lisboa; Rodrigo Bochi Motta; Fernanda Zapater Pierre (Journal of Dentistry And Oral Implants, 2018)
Currently, patients seeking dental treatment are increasingly concerned with the esthetics. Accordingly, the professional must be able to indicate treatment approaches that often include more than one specialty. This concept of integrated dentistry allows achieving excellence in results, which may not be reached one single Dentistry specialty. In addition, the multidisciplinary dentistry enables the solution of cases more conservatively, especially cases where aesthetics is a relevant factor. This study aimed to report a clinical case showing esthetic disharmony of the anterior teeth even after the ending of the orthodontic treatment, causing dissatisfaction for both the patient and the dentist. From a functional point of view, the occlusion was adequate. However, the esthetics prevented a satisfactory outcome. To solve this issue, the case was treated through minimally-invasive ceramic laminates, then reaching the expected result.
Keywords: Orthodontics